2018
DOI: 10.1016/j.jpainsymman.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Pain: Nurses' Assessment of Patient Suffering, Dignity, and Dying in the Intensive Care Unit

Abstract: ContextDeaths in the intensive care unit (ICU) are increasingly common in the U.S., yet little is known about patients’ experiences at the end of life in the ICU.ObjectivesThe objective of this study was to determine nurse assessment of symptoms experienced, and care received by ICU patients in their final week, and their associations with nurse-perceived suffering and dignity.MethodsFrom September 2015 to March 2017, nurses who cared for 200 ICU patients who died were interviewed about physical and psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 45 publications
3
41
0
1
Order By: Relevance
“…All of the measures below have been validated in prior published work. [14] DNR order status. The information about DNR orders was collected via inpatient electronic medical record systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the measures below have been validated in prior published work. [14] DNR order status. The information about DNR orders was collected via inpatient electronic medical record systems.…”
Section: Methodsmentioning
confidence: 99%
“…Results from our recently published report on nurse perception of suffering at the end of life in the ICU did not demonstrate an association between DNR status and quality of death, but did not distinguish early from late DNR. [14] Few studies have examined the timing of DNR orders and its association with mortality, length of stay, interventions, and cost. [15][16][17][18] To our knowledge, no previous studies have reported associations between DNR timing and patient-centered outcomes, such as physical or emotional distress, peacefulness, suffering or loss of dignity.…”
Section: Introductionmentioning
confidence: 99%
“…From these conceptions of dignity, we can now infer that the article by Su et al 1 was referring to an extrinsic view of dignity. As an example, the authors said that the use of feeding tubes and some symptoms such as broken skin were associated with loss of dignity.…”
mentioning
confidence: 91%
“…First, I want to suggest a reflection on the many meanings of the concept of dignity. This reflection will then help explain how the lack of an explicit definition may have influenced the findings of the research of Su et al 1 What do the authors mean by dignity? Why and how does someone lose or gain dignity?…”
mentioning
confidence: 99%
See 1 more Smart Citation